Big data : a tutorial-based approach - Raheem, Nasir (Boca Raton : CRC Press, 2019)
"This book explores the tools and techniques to bring about the marriage of structured and unstructured data. It focuses on Hadoop Distributed Storage and MapReduce Processing by implementing (i) Tools and Techniques of Hadoop Eco System, (ii) Hadoop Distributed File System Infrastructure, and (iii) efficient MapReduce processing. The book includes Use Cases and Tutorials to provide an integrated approach that answers the 'What', 'How', and 'Why' of Big Data"--
CONCLUSIONChapter 9: Data Virtualization; OVERVIEW; Conclusion: Flexibility and Agility; Pre-Installation Steps to Set Up Denodo Development Environment; CONCLUSION; Chapter 10: Cloud Computing; OVERVIEW; A QUICK GLANCE AT CLOUD COMPUTING; Software as a Service (SaaS); Platform as a Service (PaaS); Infrastructure as a Service (IaaS); CLOUD COMPUTING VERSUS HADOOP PROCESSING; CLOUD SERVICE MOST SUITED FOR BIG DATA; Infrastructure as a Service (IaaS); Advantages of IaaS; CONCLUSION; SELF-ASSESSMENT QUIZ; ANSWERS TO THE SELF-ASSESSMENT QUIZ; REFERENCES; INDEX
OCLC-licensed vendor bibliographic record.
Keywords: Big data -- Programmed instruction; COMPUTERS / Databases / General; COMPUTERS / General; COMPUTERS / Data Processing / General; COMPUTERS / Database Management / General